Are midwives ready to provide quality evidence-based care after pre-service training? Curricula assessment in four countries-Benin, Malawi, Tanzania, and Uganda. - Ann-Beth Moller; Joanne Welsh; Elizabeth Ayebare; Effie Chipeta; Mechthild M Gross; Gisele Houngbo; Hashim Hounkpatin; Bianca Kandeya; Beatrice Mwilike; Gorrette Nalwadda; Max Petzold; Antoinette Sognonvi; et al. (PLOS Global Public Health, 2022)
This research sought to map midwifery pre-service training curricula as part of the Action Leveraging Evidence to Reduce perinatal morTality and morbidity in sub-Saharan Africa (ALERT) project conducted in Benin, Malawi, Tanzania, and Uganda. We conducted the review in two phases. In the first phase, online interviews were performed with the lead project midwives in all four study countries to get an overview of midwifery care providers' pre-service training courses, registration, and licensing requirements. We performed a mapping review of midwifery care providers' pre-service training curricula from different training institutions in the four study countries during the second phase. Curricula were reviewed and mapped against the International Confederation of Midwives (ICM) Essential Competencies framework to assess whether these curricula included the minimum essential training components described in the ICM framework. We identified 10 different professional titles for midwifery care providers. The number of years spent in pre-service training varied from one and a half to four years. Ten pre-service curricula were obtained and the assessment revealed that none of the curricula included all ICM competencies. Main gaps identified in all curricula related to women-centred care, inclusion of women in decision making, provision of care to women with unintended or mistimed pregnancy, fundamental human rights of individuals and evidence-based learning. This review suggests that there are skills, knowledge and behaviour gaps in pre-service training curricula for midwifery care providers when mapped to the ICM Essential Competencies framework. These gaps are similar among the different training courses in participating countries. The review also draws attention to the plethora of professional titles and different pre-service training curricula within countries. Trial registration: PACTR202006793783148-June 17th, 2020.